Piper velaudhanii (Piperaceae), a New Name for P. Pseudonigrum Velay. & Amalraj (Journal of Scientific Research, 2013)
A new name, Piper velaudhanii, is proposed for Piperpseudonigrum described by K. C. Velayudhan and V. A. Amalaraj from Kerala, India, which happens to be a later homonym of P. pseudonigrum C.DC. from Vietnam. Keywords: Piper velayudhanii; New name; India.  © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.  doi: http://dx.doi.org/10.3329/jsr.v5i3.14237 J. Sci. Res. 5 (3), 579-580 (2013)